Dynamics of accumulation of heavy metals in Lissachatina fulica living in contaminated geographical area of East Kazakhstan - Kydyrmoldina, A.Sh.; Muratkanova, N.S.; Tursynkhan, Y.M; Oberkulova, L.A.; Yessimbekov, Zh.E.; Malik, M.M.; Zhairbaeva, R.S. (Fundamental and Experimental Biology, 2024)
In the article presents the results of a study of the dynamics of the accumulation of heavy metals and macroelements in the body of snails in the vicinity of the Ulbi metallurgical plant in the city of Ust-Kamenogorsk, East Kazakhstan region, where heavy metals are found in large quantities. Experimental work was carried out on 40 Lissachatina fulica snails over a period of 48 days. During the work, the snails were fed with soil contaminated with heavy metals and macroelements, and the dynamics of the accumulation of chemical elements in the snails’ bodies were studied every week. In the course of studying the accumulation of macroelements and heavy metals, experimental animals were prepared using the method of two-stage euthanasia in compliance with ethical standards. During the study, mass spectrometry (ISP-MS) analyzed the amount of elements Ca, K, Mg, N, V, Co, Pb, As, Sr, Cu, Zn in the bodies of intact animals, control and research groups. A large amount of heavy metals and macroelements was found in the body of the animals of the research group. The amount of heavy metals accumulated in the body of snails increased on the 32nd day and then decreased again (P<0.001). According to research results, it is known that heavy metals accumulate in the body in one month, which means that this environmental situation is one of the problems that requires an urgent solution. Although the accumulation of heavy metals in the soil of geographical area and their amount in the soil were studied, their accumulation in living organisms, including snails, and the dynamics of their accumulation as a result of many years of research have been studied for the first time.